2008
DOI: 10.2516/ogst:2008025
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Phenomena in Association Theories with Applications to Oil & Gas and Chemical Industries

Abstract: Résumé -Les théories d'association et le phénomène de la solvatation : application aux industries du pétrole et du gaz, et à la pétrochimie -Les théories de l'association issues de la famille des équations SAFT (Self Associating Fluid Theory) expriment explicitement le phénomène de l'autoassociation ainsi que de l'association croisée. Ces phénomènes ont une grande importance pratique car ils ont un effet souvent majeur sur l'équilibre de phases de nombreux mélanges d'intérêt industriel. D'un point de vue scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…The above observations correspond well with the findings of Kontogeorgis et al [47], who applied the CPA EoS to model liquid-liquid equilibria of two linear ethers (di-n-propylether and ethyl propylether) in their binary mixtures with water. Water was assigned an association scheme with two electron donating and two electron accepting sites, while both ethers were assumed to be non self-associating.…”
Section: Predicted Llesupporting
confidence: 87%
“…The above observations correspond well with the findings of Kontogeorgis et al [47], who applied the CPA EoS to model liquid-liquid equilibria of two linear ethers (di-n-propylether and ethyl propylether) in their binary mixtures with water. Water was assigned an association scheme with two electron donating and two electron accepting sites, while both ethers were assumed to be non self-associating.…”
Section: Predicted Llesupporting
confidence: 87%
“…The CPA EoS has been extensively applied in the literature to model the phase behaviour of various associating systems [81,84,[93][94][95][96][97] and has been shown to be able to provide a correct description of the system under investigation over a wide range of experimental conditions [82,98]. Although CO 2 can be regarded as a non-associating compound, the findings of Tsivintzelis et al [82] revealed the importance of taking into consideration the specific strong interactions between CO 2 and water, mainly Lewis electron donor-acceptor type.…”
Section: Phase Equilibrium Modelmentioning
confidence: 99%
“…Comparing Figure 17 to Figure 8 of ref 106, it can be seen that the phase diagrams are quite similar, with one phase (aqueous) consisting mostly of water and the organic phase having 20−40% benzoic acid and 20−60% cresol. The LLE region for water−mcresol is in the range of 300−410 K, whereas it is at somewhat lower temperatures (350−385 K) for water−benzoic acid.…”
Section: How Important Is It To Consider Polarity For Phase Behavior mentioning
confidence: 79%